Functionalization of Metallic Magnesium with Protein Layers via Linker Molecules - Killian, Manuela; Wagener, Victoria; Schmuki, Patrik; Virtanen, Sannakaisa (Langmuir, 2010)
We present an innovative method to cover pure magnesium with protein monolayers by utilizing the OH termination of the oxide surface and silane coupling chemistry. The protein of interest was albumin. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) were used to monitor the success of the treatment. The attachment of proteins via linker groups yielded smoother and more homogeneous surfaces than coatings produced by steeping magnesium in protein solution. A positive effect on the corrosion behavior of pure magnesium was also observed.